A low‐cost treatment system for underground water using Moringa oleifera seeds and Musa cavendish peels for remote communities. Issue 3 (20th October 2020) - Aziz, Nur AA; Jayasuriya, Niranjali; Fan, Linhua; Al‐Gheethi, Adel
Abstract: BACKGROUND: Nemours plant‐based biomass exhibit higher removal capacities in comparison to chemical treatment methods. The present study aimed to investigate the potential of Moringa oleifera (MO) seeds and Musa cavendish (MC) peel biomass pre‐treated by HNO3 (1 N) and NaOH (0.1 M) for removing nickel (Ni), lead (Pb) and cadmium (Cd) ions from synthetic groundwater. It further aimed to establish the design and test the efficiency of an individual domestic groundwater treatment system with low‐cost using local materials. The batch tests with biomass (MC, MO and MC + MO) were conducted at pH 7. Adsorption was investigated using Freundlich and Langmuir models for single elements, and the Sheindorf–Rebhun–Sheintuch (SRS) model for multicontaminant elements. By contrast, the simulation of actual groundwater quality was studied using a Monte Carlo simulation model. RESULTS: The adsorption results fitted with the Freundlich model revealed that ≈91%, 98% and 84% of groundwater samples met WHO standards for Pb 2+, Ni 2+ and Cd 2+, respectively. The FTIR analysis of MC, MO and MC + MO revealed that CC, CO and NH were the main functional groups playing roles in the removal of heavy metals from the water samples. The mechanism of adsorption took place by chemisorption and physisorption. The total cost of the water treatment system with a capacity of 50 L was US17, and considered suitable for remote, lower income communities. CONCLUSION: The MC + MO biomass was efficient in adsorbing heavy metal ions from water samples owing to the presence of abundant functional groups.